2009
DOI: 10.1007/s00737-009-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific functional variant of the TPH2 gene 2755C>A polymorphism contributes risk association to major depression and anxiety in Chinese peripartum women

Abstract: The rate-limiting enzyme of serotonin biosynthesis, tryptophan hydroxylase 2 (TPH2), is one of the most promising candidate genes for psychiatric disorders. Although evidence strongly suggests that the TPH2 is significant in the etiology of major depression and anxiety disorder, whether it also contributes to the etiology of peripartum major depression and anxiety disorder, a specific subtype influenced considerably by other environmental factors like hormones, is unclear. This study investigated the role of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
3
20
0
1
Order By: Relevance
“…The TPH2 polymorphism genotype and allele frequency was found to be statically non-significant in case of anxiety disorder. Lin YM et al, and Youn JS reported association of anxiety with TPH2 polymorphism [6,19]. Similar findings have been reported earlier also [20,21].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The TPH2 polymorphism genotype and allele frequency was found to be statically non-significant in case of anxiety disorder. Lin YM et al, and Youn JS reported association of anxiety with TPH2 polymorphism [6,19]. Similar findings have been reported earlier also [20,21].…”
Section: Resultssupporting
confidence: 81%
“…It was found that patients with panic disorders had lower levels of circulating serotonin compared with controls in one study [3]. The gene of tryptophan hydroxylase, the rate limiting enzyme in the synthesis of serotonin, is widely recognized as a major candidate gene in many psychiatric disorders [4][5][6].Recently a new isoform of the enzyme (TPH2) has been identified.TPH2 is predominantly expressed in the brain stem, where the serotonergic raphe nuclei are located [4][5][6][7]. Therefore we planned to study the role of TPH2 gene in anxiety and depressive disorders in our Kashmiri population (India).…”
Section: Introductionmentioning
confidence: 99%
“…The TPH1 isoform is expressed in peripheral tissues, whereas TPH2 is brain and neuronspecific (Invernizzi, 2007;Walther et al, 2003). Two studies in Asian cohorts observed significant associations between single variants in the tryptophan hydroxylase (TPH) isoform 1 and 2 genes TPH1 and TPH2 and postpartum depression, in a caseecontrol design (Lin et al, 2009;Sun et al, 2004), but no association for polymorphisms in these genes was reported in larger Spanish study (Costas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence for the importance of tryptophan in peripartum depression (Kohl et al, 2005;Maes et al, 2002), this neuronal isoform of TPH is an important candidate gene for this disorder, currently with conflicting genetic association data from only two studies (Costas et al, 2010;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Investigações em humanos encontraram correlações entre variações genéticas no gene da Tph2 com aumento da incidência de casos clínicos de depressão e suicídio (Zill et al, 2004a(Zill et al, , 2004b, com o risco de desenvolver quadro de ansiedade/depressão em mulheres em período peri-parto (Lin et al, 2009), bem como com a ocorrência de autismo (Coon et al, 2005).…”
Section: Sistema Serotoninérgico E Comportamentos Emocionaisunclassified